Variants in PCSK7, PNPLA3 and TM6SF2 are risk factors for the development of cirrhosis in hereditary haemochromatosis. Issue 7 (10th February 2021) - Buch, Stephan; Sharma, Aneesh; Ryan, Eleanor; Datz, Christian; Griffiths, William J. H.; Way, Michael; Buckley, Thomas W. M.; Ryan, John D.; Stewart, Stephen; Wright, Callum; Dongiovanni, Paola; Fracanzani, Anna; et al.
Summary: Background: Cirrhosis develops in <10% of individuals homozygous for the C282Y variant in the homeostatic iron regulator ( HFE ) gene. Carriage of PCSK7 :rs236918 is associated with an increased risk of cirrhosis in this population. Aim: To determine if genetic variants significantly associated with the risk of alcohol‐ and NAFLD‐related cirrhosis also modulate the cirrhosis risk in C282Y homozygotes. Methods: Variants in PCSK7, PNPLA3, TM6SF2, MBOAT7 and HSD17B13 were genotyped in 1319 C282Y homozygotes, from six European countries, of whom 171 (13.0%) had cirrhosis. Genotypic and allelic associations with the risk for developing cirrhosis were assessed, adjusting for age and sex. Fixed effects meta‐analyses of the adjusted summary data for each country were performed. Post hoc association testing was undertaken in the 131 (76.6%) cases and 299 (26.0%) controls with available liver histology. Results: Significant associations were observed between PCSK7 :rs236918 (OR = 1.52 [95% CI 1.06‐2.19]; P = 0.022; I 2 = 0%); PNPLA3 :rs738409 (OR = 1.60 [95% CI 1.22‐2.11]; P = 7.37 × 10 −4 ; I 2 = 45.5%) and TM6SF2 :rs58542926 (OR = 1.94 [95% CI 1.28‐2.95]; P = 1.86 × 10 −3 ; I 2 = 0%) and the cirrhosis risk in C282Y homozygotes. These findings remained significant in the subpopulation with available liver histology. The population‐attributable fractions were 5.6% for PCSK7 :rs236918, 13.8% for PNPLA3 :rs738409, 6.5% for TM6SF2 :rs58542926 and 24.0% for carriage of all three variants combined. Conclusions: The risk of cirrhosis associated with carriage of PCSK7 :rs236918 was confirmed in this much larger population of C282Y homozygotes. In addition, PNPLA3 :rs738409 and TM6SF2 :rs58542926 were established as significant additional risk factors. More detailed genetic testing of C282Y homozygotes would allow risk stratification and help guide future management.